IMPACT EVALUATION OF LITERACY ON HEALTH IN SCHOOL FROM THE THIRD CYCLE OF BASIC EDUCATION: A SCOPING REVIEW - Dias, Hélia; Amendoeira, José; Spínola, Ana; Figueiredo, Maria do Carmo; Godinho, Celeste; André, Clara; Duarte, Jusoé; Pintor, Marta; Ferreira, Madalena (Revista da UI_IPSantarém, 2020)
The scientific evidence shows the importance of promoting health for eating, sexuality, tobacco and alcohol use among teenagers. There is no evidence to assess its impact. Aim: identify instruments to measure the impact of interventions to promote healthy diet, sexuality, tobacco and alcohol use among teenagers. Method: Scoping review based on Participants, Concept, Context, from Joanna Briggs Institute method. Results: The studies were selected following the PRISMA, and the data was extracted. Six primary studies were included; five were quantitative in design; the other was of mixed design. Instruments were identified that would make it partially possible to assess the impact of interventions of healthy eating and tobacco and alcohol use. The topic of sexuality did not arise. Conclusion: Some variables emerged from the instruments identified, that were relevant in building an instrument to assess the impact of interventions to promote healthy diet, sexuality, tobacco and alcohol use among teenagers.